Novel Strategy for Optimized Nanocatalytic Tumor Therapy: From an Updated View. Issue 7 (3rd June 2022) - Li, Zhen-Li; Wu, Han; Zhu, Jia-Qi; Sun, Li-Yang; Tong, Xiang-Min; Huang, Dong-Sheng; Yang, Tian
Abstract : Nanozyme has been experiencing rapid development in biomedical applications involving biosensors, immunoassays, and antitumor agents in recent years due to its tunable catalytic performance and desirable biocompatibility. Since the first exploration of nanozyme‐based Fenton reaction for nanocatalytic therapy (NCT) against tumor, a variety of Fenton (and Fenton‐like) nanozymes, such as Fe3 O4, transition metal ions (Co 2+, Cu 2+, and Mn 2+ ), and metal–organic frameworks (MOFs), have been proved as desirable candidates for tumor therapy, and the modulation of the tumor microenvironment (TME) is determined to be a feasible approach to improve the catalytic efficiency for in situ tumor suppression. At present, increasing studies have focused on improving the therapeutic efficiency of NCT by formulating multifunctional nanozyme‐based systems to satisfy the demand for versatile and optimized applications. Herein, updated insights into the novel strategies of 1) achieving highly effective nanocatalytic reactions, including the modification of nanocatalysts and TME‐modulating approaches, are provided and 2) the design and formulation of multifunctional nanozyme‐based systems which achieve targeted, synergistic therapy, and theranostic applications are analyzed and concluded. Concise and concentrated comments and outlooks are illuminated at the end to outline the perspectives and the remaining challenges for the next‐step explorations on further biomedical translation of NCT. Abstract : With the rapid development of nanocatalytic tumor therapy, the review provides updated insights into the novel strategies of optimized nanocatalytic therapy in the following aspects: 1) achieving highly effective nanocatalytic reactions, including the modification of nanocatalysts and tumor microenvironment‐modulating approaches and 2) the design and formulation of multifunctional nanozyme‐based systems which achieve targeted, synergistic therapy, and theranostic applications.